Analysis of workforce needs in the medical records unit at Esthomihi Hospital Medan using the queuing theory approach - Ginting, Sopianita Healthy; Girsang, Ermi; Nasution, Sri Lestari Ramadhani (Institute of Computer Science (IOCS), 2025)
Medical records are important records that contain all information related to services that have been provided to patients. The less than optimal process of implementing medical records can be due to a lack of human resources, training, or supporting facilities and infrastructure. This study aims to analyze the need for workers in the medical records department of the hospital with a theoretical approach (queueing theory) at Esthomihi Hospital Medan. This type of research is quantitative with an analytical observational approach. The research design used is cross sectional. This study was conducted at Esthomihi Hospital in December-January 2025. In this study were all health workers related to the implementation of medical records consisting of doctors, nurses, medical records officers and pharmacists at Esthomihi Hospital Medan as many as 252 people. The sample in this study were all doctors, nurses, medical records officers and pharmacists related to patient medical records at Esthomihi Hospital Medan as many as 252 people. Data analysis was carried out univariately, bivariate and multivariate. The results of the study indicate that there is an influence of the level of patient arrivals, the level of patient service, the number of patient servers, and the system capacity. The most influential variable on the need for manpower in hospital medical records affairs with a theoretical approach (queueing theory) at Esthomihi Hospital Medan is the variable number of patient servers with ap value of 0.000, OR = 125.571 (95% CI = 25.114-627.866) meaning that respondents who stated that the number of patient servers was lacking a 125.571 times less chance compared to respondents who stated that the number of patient servers was good n It is expected to be able to improve, expand, develop, experience and knowledge directly regarding the need for manpower in hospital medical records affairs with a theoretical approach (queueing theory) at Esthomihi Hospital Medan.